A new proof for the security of the keyed Sponge construction in the ideal compression function model - Nguyen, Anh Tuan; Nguyen, Cuong Bui (Journal of Science and Technology on Information security, 2020)
Abstract— In this paper, we present a new proof for the security of keyed Sponge. Our method is built on the previous result about the indistinguishability of the Sponge construction. Following this approach, we can see the strong relationship between the security of keyed Sponge and its original version. Tóm tắt— Trong bài báo này, chúng tôi đưa ra một chứng minh mới cho độ an toàn của cấu trúc Sponge có khóa. Phương pháp của chúng tôi sử dụng kết quả trước đó về tính không phân biệt được của cấu trúc Sponge. Theo cách tiếp cận này, chúng ta có thể thấy mối liên hệ chặt chẽ về độ an toàn của cấu trúc Sponge có khóa và phiên bản nguyên thủy của nó.